СОДЕРЖАНИЕ БИОЛОГИЧЕСКИ АКТИВНЫХ ВЕЩЕСТВ СМЕШАННЫХ КУЛЬТУР МИКРОВОДОРОСЛЕЙ ПРИ СОВМЕСТНОМ КУЛЬТИВИРОВАНИИ (Experimental biology, 2017)
The experimental data combined cultivation of are mixed cultures of microalgae on the modified environments. Presented the results of experiment show that during the cultivation of the mixed cultures of microalgae on the modified environments were observed speed enhancing of cell growth and accordingly with the increase of bioactive substances as compared with control.
Keywords: bioactive substances; microalgae